Handbook of blockchain law a guide to understanding and resolving the legal challenges of the blockchain technology - Artzt, Matthias, 1968-; Richter, Thomas, 1967- (Kluwer Law International B.V., 2020)
"Handbook of Blockchain Law provides an overview of the key features and functionalities of blockchain technology in a legal context in a remarkably descriptive way. Blockchain has become attractive to companies and governments as it promises to solve the age-old problem of mutability in transactions. That is, it makes falsification and recalculation impossible once a transaction has been committed to the technology. The systematic and comprehensive approach set forth in this book, including coverage of existing relevant law in various jurisdictions with a particular focus on European law and US law and practical guidance on how to tackle legal issues raised by the use of blockchain, ensures a one-stop-shop reference book for anyone considering blockchain-based solutions or rendering advice for them"--